An investigation into the representation of geological maps by 15–16 year‐old Turkish students - Dal, Burckin (Informa UK Limited, 2010)
This paper explores secondary school students’ representations of a geological map. Ninety‐two high school students (ninth graders – 15‐ to 16‐years‐old) participated in the survey in Turkey. The findings indicate that students have only a vague idea of how a geological map is constructed, and how the map is affected by the topography. The students’ poor understandings are based on insufficient information supplied to them during their learning process, and on their need to see things clearly in order to describe or understand them. Since research shows that developing an understanding of how to make and use geological maps fosters the development of cognitive skills in general, the implication of these research findings is that all pupils would benefit from education in how to make and use geological maps. Thus national curricula should require training in geological map work, teachers should be trained in teaching the necessary skills and textbooks should include good coverage of this topic.